Forensic Medical Evaluation of Acute Desomorphino Poisoning with Pathological Changes in Internal Organs (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
the study of the results of clinical and laboratory studies in cases of acute poisoning with semi-synthetic drugs desomorphine (Crocodile) showed that the most effective methods of their detection are toxicological analysis and gas-liquid chromatography. During forensic medical examinations, pathomorphological signs on internal organs, characteristic in such cases for acute poisoning, became a clear manifestation. Including transfusion of reddish and purple blood with large and small dots on the internal organs, the dura mater.